2009
DOI: 10.2147/ppa.s7906
|View full text |Cite
|
Sign up to set email alerts
|

Reducing adverse self-medication behaviors in older adults with the Next Generation Personal Education Program (PEP-NG): Design and methodology

Abstract: A randomized controlled efficacy trial targeting older adults with hypertension is providing a tailored education intervention with a Next Generation Personal Education Program (PEP-NG) in primary care practices in New England. Ten participating advanced practice registered nurses (APRNs) completed online knowledge and self-efficacy measures pre-onsite training and twice more after completing a continuing education program. Patient participants self-refer in response to study recruitment brochures and posters.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…Mild to moderate improvement in self-efficacy was reported in previous studies using pictorial aids with interaction Neafsey et al, 2009). This demonstrated that the use of an educational aid, such as visual materials with active interaction, allowed older adults to use medication appropriately and increased their confidence.…”
Section: Discussionsupporting
confidence: 60%
“…Mild to moderate improvement in self-efficacy was reported in previous studies using pictorial aids with interaction Neafsey et al, 2009). This demonstrated that the use of an educational aid, such as visual materials with active interaction, allowed older adults to use medication appropriately and increased their confidence.…”
Section: Discussionsupporting
confidence: 60%
“…24, 25 The trial was approved by the University Institutional Review Board (IRB) and met all HIPAA regulations prior to enrolling any provider or patient participants. The PEP-NG was tested with 160 older adults with HTN in 10 APRN primary care practices.…”
Section: Introductionmentioning
confidence: 99%
“…Although education related to self-medication is provided at schools, [20][21][22][23] in reality, self-medication itself is not widely disseminated to the public, and appropriate self-medication is not being conducted. 9,[24][25][26][27] Therefore, it seems clear that continuous, effective education regarding appropriate self-medication is necessary for adults. However, although there have been reports on the efficacy of self-medication education for patients with hypertension, 28,29) few studies have examined the efficacy of selfmedication education for adults in general.…”
Section: Introductionmentioning
confidence: 99%